Application of molecular interaction volume model in separation of Sn-Zn alloy by vacuum distillation - Kong, Ling-xin; Yang, Bin; Li, Yi-fu; Xu, Bao-qiang; Han, Long; Liu, Da-chun; Dai, Yong-nian (Journal of Central South University, 2013)
The activity of components of Sn-Zn binary alloy system was predicted based on the molecular interaction volume model (MIVM). The calculated values are in good agreement with available experimental data of activities, which indicates that this model is of stability and reliability because the MIVM has a good physical basis. The vapor-liquid phase equilibrium of Sn-Zn alloy system in vacuum distillation was calculated as a function of the activity coefficient. The results show that the content of Sn in vapor phase is 4.2×10 −7 (mass fraction) while in liquid phase it is 90% (mass fraction) at 1 073 K, and the content of Sn in vapor phase increases with increasing the melt temperature and content of Sn in liquid phase. Vacuum distillation experiments were carried out on Sn-Zn alloy for the proper interpretation of the results of the MIVM in the temperature range of 973–1 273 K under pressures of 15–200 Pa. The experimental results show that the content of Sn in vapor phase is 5×10 −6 (mass fraction) while in liquid phase it is 90% (mass fraction) under the operational condition of 1 073 K, 100 min and 15 Pa. The experimental results are in good agreement with the predicted values of the MIVM for Zn-Sn binary alloy system.